1969
DOI: 10.12669/pjms.303.4648
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nosocomial infections among children with congenital heart disease

Abstract: Objective: To study the pathogen distribution, antimicrobial susceptibility and risk factors of postoperative nosocomial infections among children with congenital heart disease. Methods: Three hundreds children with congenital heart disease admitted to our hospital to receive surgeries from February 2010 to February 2013 were selected. Results: A total of 120 children were tested as positive by sputum culture, with the infection rate of 40.0%. The top five most common pathogenic microorganisms included Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Surgery is the main treatment for most heart defects [14]. But pediatric cardiac surgery reduces the patient's immunity and increases the risk of postoperative infection [15]. The study found that nosocomial infection was one of the main complications in the postoperative period in children with CHD, and are major causes of morbidity and mortality after cardiac surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the main treatment for most heart defects [14]. But pediatric cardiac surgery reduces the patient's immunity and increases the risk of postoperative infection [15]. The study found that nosocomial infection was one of the main complications in the postoperative period in children with CHD, and are major causes of morbidity and mortality after cardiac surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for ventilator-associated pneumonia were PRISM III score > 10 and transfusion of fresh-frozen plasma. 12 Epidemiology of perioperative infections in low-and middle-income countries Among 21 studies in low-and middle-income countries, four were conducted in China, [43][44][45][46] four in India, [47][48][49][50] three in Brazil, [51][52][53] two in Saudi Arabia 54,55 , and one each in Argentina, 56 Bosnia Herzegovina, 57 Iran, 58 Ethiopia, 59 Guatemala, 60 and Sudan. 61 One multicentre study involving 17 low-to middle-income countries included India, Pakistan, Colombia, Russia, China, Dominican Republic, Brazil, Argentina, El Salvador, Ukraine, Peru, Mexico, Belarus, Vietnam, Uganda, Guatemala, and Bangladesh.…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
“…62 There were five different study designs including one randomised controlled trial, 53 one non-randomised interventional before-after study, 62 16 cohort studies, [43][44][45][47][48][49][50]52,[54][55][56][57]59,60,63 one case-control study, 51 and three cross-sectional studies. 46,58,61 Most studies were conducted in children, with two in neonates 47,57 and two involving children and adult patients. 43,50 Preoperative infection There were seven studies evaluating preoperative infections among children with CHD in low-to middle-income country settings.…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
See 2 more Smart Citations